Effect of Different Pulse Treatments on Vase Life of Inflorescences of Oncidium varicosum 'Samurai' - Mattiuz, C. F. M.; Mattiuz, B. H. [UNESP]; Pietro, J. [UNESP]; Rodrigues, T. J. D. [UNESP]; Cantwell, M. I.; Almeida, DPF (Int Soc Horticultural Science, 2012)
Oncidium varicosum is a species of orchid that is prevalent in South America. This species produces yellow flowers, which are commonly named golden shower, ballet dancer and Anita's flower. The study of the post-harvest physiology of flowers involves examination of factors related to quality loss of cut flowers, which is related not only to several physiological processes but also to interactions between the floral components and qualitative factors. In this context, our research involved the study of physiological aspects of the post-harvest physiology of cut inflorescences of Oncidium varicosum ('Samurai') after treatment with pulsing solutions containing silver salts, 8-HQC and sucrose. A reduction of relative water content of Oncidium flowers treated with pulsing STS (2 mM) was observed. The soluble carbohydrates and reducing sugars content decreased, and higher contents were measured in flowers treated with STS (2 mM). All parameters related to flower coloration were reduced in all treatments. Similar results were obtained for carotenoid content, except for the STS treatment (2 mM), which differed significantly from the other treatments on the 8th and 12th days of vase life. The inflorescences' longevity varied from 12 days (distilled water) to 15 days (STS 2 mM).
Keywords: postharvest physiology; orchids; carbohydrates; carotenoids